Comparative study of five anti-lipopolysaccharide factor genes in Litopenaeus vannamei. (February 2023) - Yin, Chenlin; Shen, Xiaojing; Wang, Yan; Hu, Jingjie; Bao, Zhenmin; Wang, Mengqiang
Abstract: Anti-lipopolysaccharide factors (ALFs) are a family of common innate immune effectors in crustaceans, and they exhibit broad spectrum antimicrobial activity. In this study, we identified and characterized five novel ALF genes (designated as Lv ALF1–5) from the Pacific white shrimp ( Litopenaeus vannamei ) to investigate their potential immune functions. The amino acid sequence alignments showed that Lv ALFs contained two conserved cysteine residues, a hydrophobic N-terminal region, and the conserved signature sequence W(T/K)CPG(S)WT(A). They all shared high similarity with previously reported ALFs and were clearly novel members of the ALF family. The mRNA transcripts of Lv ALFs were most highly expressed in hemocytes and the hepatopancreas. After shrimp were stimulated with Vibrio parahaemolyticus or white spot syndrome virus, expression of the Lv ALFs was significantly induced in hemocytes and the hepatopancreas with various expression profiles. Recombinant proteins of Lv ALFs exhibited potent bacteriostatic activity in vitro . Together, these results suggest that Lv ALF1–5 participate in the immune response of Pacific white shrimp against invading pathogens. Highlights: Five novel ALFs have been identified from Litopenaeus vannamei, and were highly expressed in hemocytes and hepatopancreas. Lv ALFs could be significantly induced by the stimulation of Vibrio parahemolyticus or white spot syndrome virus. Recombinant proteins of Lv ALFs exhibited potent bacteriostatic activity in vitro .